A cyano-bridged tubular coordination polymer with dominant ferromagnetic interactions. Issue 2 (10th November 2014) - Zhuang, Peng-Fei; Liu, Tao; Xie, Xian-Hui; He, Cheng; Duan, Chun-Ying
Abstract : Utilizing [Fe II (bipy)(CN)4 ] 2− as the building block to react with Mn II, we successfully synthesized a tubular coordination polymer with dominant ferromagnetic interactions. Moreover, the framework shows high thermal stability. Abstract : It is a challenge to synthesize a porous tubular coordination polymer with magnetic properties. Utilizing [Fe II (bipy)(CN)4 ] 2− (bipy = 2, 2′-bipyridine) as the building block to react with Mn 2+, we successfully synthesized a cyano-bridged tubular coordination polymer with dominant ferromagnetic interactions. The inner surface of the heterometallic tube is hydrophilic, whereas the outer surface is hydrophobic. The framework is stable up to 320 °C and can adsorb N2 and CO2 . The ferromagnetic interactions were transmitted via the diamagnetic N–C–Fe II –C–N species between Mn 2+ ions in the tube.